Child Marriage and Faith Affiliation in Sub-Saharan Africa : Stylized Facts and Heterogeneity - Gemignani, Regina (Taylor and Francis, 2015)
This article has two main objectives. First, it provides an account of trends in child marriage in Africa and a brief analysis of the statistical association between child marriage and faith affiliation. Second, it cautions against broad generalizations about child marriage and faith affiliation, in order to show that beyond stylized facts derived from household survey data, there is also substantial heterogeneity within the adherents of any particular faith as to how the practice of child marriage is considered. The analysis focuses on Islamic communities.